Integrated Approach of QFD Matrix, Servqual and Kano Models For Human Resources Analysis in Non Star Hotel Service Quality - Eka Rakhmat Kabul; Marhalinda Marhalinda; Herminda Herminda; Nurina Nurina; Harry Ganda Wijaya (Return : Study of Management, Economic and Bussines, 2023)
The hotel industry, especially non-star hotels, is experiencing the development of very tight competition where consumers prioritize service quality in addition to very low prices, which demands the readiness of their human resources. Identify and analyze matters that need to be considered by lodging managers regarding consumer perceptions of the quality of lodging services for service improvement and increasing the readiness of its human resources. This research uses an integrated approach from the QFD Matrix, Servqual and the Kano Model to find out what things (WHATs) are the main problems of consumer complaints and how (HOWs) overcome these consumer complain its focusing on the human resource aspect. There were 16 service attributes from the results of interviews with consumers and brainstorming with inn managers which were then analyzed using the Servqual and Kano Model, it turned out that 10 service attributes did not meet the level of customer expectations and became the WHATs submatrix in QFD. The largest Level of Interest and Percentage of Interest in the HOW sub-matrix (above 10%) is on human resource issues so that service quality improvements are focused on these matters. The research is limited to the case of one of the cheap lodgings as well as limitations on interviews with respondents and hotel managers who are determined randomly. Analysis of service quality was carried out on all service attributes from the results of interviews, but the discussion was only discussed on service attributes that had the highest interest percentage above 10% in the aspect of human resources. Research on human resource aspects of service quality in the hospitality industry by integrating the QFD Matrix, Servqual and Kano Models.